Setting the photoelectron clock through molecular alignment - Andrea Trabattoni (Nature Portfolio, 2020)
Interaction of strong laser fields with matter provides powerful tools to image transient dynamics with high spatiotemporal resolution. The authors investigate strong-field ionisation of laser-aligned molecules showing the effect of molecular alignment on the photoelectron dynamics and the resulting influence of the molecular frame in imaging experiments.